Literacy on Pregnancy Complications: Causal Factors and Prevention - Tahira, Tahira; Fatima, Deviani (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study investigates the role of maternal health literacy in preventing pregnancy complications and evaluates the effectiveness of various educational interventions designed to enhance health literacy. Research Design and Methodology: This research employed a quantitative design, utilizing pre-and post-tests to measure changes in knowledge, skills, and attitudes among diverse demographic participants. Participants were divided into two groups: control and experimental. Educational interventions were implemented, including prenatal classes, online courses, and community workshops. Data were collected through surveys and analyzed using statistical methods. Findings and Discussion: The study revealed a significant correlation between increased health literacy and reduced pregnancy complications such as pre-eclampsia, gestational diabetes, and preterm labor. This positive correlation underscores the potential for improved maternal and child health outcomes. Educational interventions significantly enhanced health literacy, with different models showing varied effectiveness based on accessibility and engagement. These findings align with the Health Belief Model and Self-Determination Theory, reinforcing the positive impact of health literacy on maternal and child health outcomes. Implications: The research underscores the importance of tailored educational interventions in promoting maternal and child health. Policymakers and healthcare providers should prioritize developing comprehensive, accessible, culturally sensitive health education programs. Addressing socio-economic disparities and providing continuous support is crucial to ensuring that all mothers and children have equal access to healthcare and can benefit from improved health literacy. Future research should investigate the long-term effects of innovative educational technologies to enhance maternal health outcomes further.